Experiencing Human Rights Protections in Prisons: The Case of Prison Monitoring in Ireland - Rogan, Mary (My University, 2020)
The protection of human rights in prison gives rise to unique challenges. The power differentials and dynamics involved, the need to balance considerations of security with those of dignity, and the lack of openness to the outside world mean that the implementation of human rights principles takes on a particular importance in these environments. International human rights law has increasingly emphasized the importance of external oversight of prisons as a way to prevent torture and ill-treatment and to uphold fundamental rights more generally. Although the monitoring of prisons is now quite well established as a principle of European and international human rights provisions, we know surprisingly little about how people in prison experience and understand monitoring bodies. This gap in our understanding is part of a wider lack of literature on how prisoners experience their rights and protections of their rights. This article addresses that gap a, reporting on qualitative findings from a study with people in prison in Ireland on their views and perceptions of a monitoring body: the Inspector of Prisons. The article finds evidence of a lack of awareness of, and a deficit of trust in, monitoring. However, this picture is complex, with people in prison also viewing the concept of monitoring as a good way to protect rights, believing that the visibility of monitors, clarity in their role and powers, and ensuring that a variety of voices are heard by monitoring bodies are important elements of a good system of prison oversight.
PUBLISHED
Keywords: Human rights and imprisonment; OPCAT; Mandela Rules; European Prison Rules; Prison monitoring